2015
DOI: 10.1007/s00586-015-4217-2
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the spinopelvic factors on the pelvic inclination from standing to sitting before total hip arthroplasty

Abstract: The change in pelvic inclination from standing to sitting is strongly related to the mobility of the lumbar spine in patients with hip diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 44 publications
3
50
0
Order By: Relevance
“…In general, PT changes posteriorly from supine to standing position. Preoperative assessment with a dynamic evaluation in the standing and sitting or supine position reduces the risk of complications. Second, PT changes posteriorly over the years after THA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, PT changes posteriorly from supine to standing position. Preoperative assessment with a dynamic evaluation in the standing and sitting or supine position reduces the risk of complications. Second, PT changes posteriorly over the years after THA.…”
Section: Discussionmentioning
confidence: 99%
“…Cup inclination and anteversion angles were targeted at 35°–45° and 15°–25°. Cup orientation is affected by the pelvic tilt (PT), and several studies have demonstrated the postural change in PT between sitting, supine and standing position. Postoperative change in PT is important for accurate preoperative planning of acetabular cup angles.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that patients with hip osteoarthritis demonstrated abnormal hip kinematics during daily activity [7,8]. Moreover, other studies reported that spinal fusion may alter the adaptation of the spinopelvic junction [9,10]. This can result in less than optimal acetabular implant anteversion and inclination in standing and sitting positions, leading to potential dislocations or subluxations after total hip arthroplasty (THA) [3].…”
Section: Introductionmentioning
confidence: 99%
“…During sitting, the L1 slope change was relatively small (4.7°). As the kyphotic thoracic spine forms a cage in combination with the ribs and respiratory muscles, a minimal sagittal ROM (0.1°) is present, as reported by Ochi et al [8] This cage provides a stable base for the cervical spine and head. Below L1, the lumbar spine, pelvis, and femur rotate in a chain-like manner to distribute the flexion of the spinofemoral movement [21].…”
Section: Discussionmentioning
confidence: 69%
“…The functional angles of the acetabular component in THA patients may change according to the body posture [5][6][7][8]. Studies have reported a 22.3-28.7°posterior pelvic tilt change from standing to sitting [6][7][8]. Babisch et al (2008) reported that for every 1°change in the pelvic tilt, the cup inclination and anteversion changed by approximately 0.3°and 0.8°, respectively [5].…”
Section: Introductionmentioning
confidence: 99%